Changes in coral reef communities and an associated reef fish species, Cephalopholis cruentata (Lacepede), after 30 years on Curacao (Netherlands Antilles) - Nagelkerken, I; Vermonden, K.; Moraes, OCC; Debrot, A. O.; Nagelkerken, W. P. (Springer, 2005)
Using the same methodology and identical sites, we repeat a study dating from 1973 and quantify cover of hard coral species, soft corals, sponges, hard substratum and soft substratum, and density of a commercially important reef fish species, the graysby Cephalopholis cruentata, along a depth-gradient of 3-36 m oil the coral reefs of Curacao. The objective was to determine the multi-decade change in benthic coral reef cover and structural complexity, and their effect oil densities of an associated reef fish species. Total hard coral cover decreased on average from 52% in 1973 to 22% in 2003, representing a relative decline of 58%. During this time span, the cover of hard substratum increased considerably (from 11 to 58%), as did that of soft corals (from 0.1 to 2.2%), whereas the cover of sponges showed no significant change. Relative decline of hard coral cover and of reef complexity was greatest in shallow waters (near the coast), which is indicative of a combination of anthropogenic influences from shore and recent storm damage. Cover of main reef builder coral species (Agaricia spp., Siderastrea siderea, Montastrea annularis) decreased more than that of other species, and resulted in a significant decrease in reef complexity. Although density of C. cruentata was highly correlated to cover of Montastrea and Agaricia in 1973, the loss of coral cover did not show any effect on the total density of C. cruentata in 2003. However, C. cruentata showed a clear shift in density distribution from shallow water in 1973 to deep water in 2003. It call be concluded that the reefs of Curacao have degraded considerably in the last three decades, but that this has had no major effect on the population size of one commercially important coral-associated fish species.
Keywords: coral reef degradation; coral reef communities; coral reef complexity; Serranidae; fish population structure; Caribbean